Evaluation of 3D magnification factor Mk of load carrying fillet welded joints - Chan, Vincent Kai Chun. (2010)
This study focus on the stress intensity factors for weld toe cracks in a single T-butt joint using the boundary element method. 3-D boundary element meshes models will be generated using AutoCAD software. In order to simulate real life conditions where the stress experienced intensified nearer to the crack, denser element will be used nearer to the crack tip in order to get a result that is representative of real life condition. Parametric study will then be conducted in order to better understand the effect of each parameter on the stress intensity factor. The main parameters to be studied are the attachment footprint ratio, L/T, and also its components, the weld leg length, w and attachment thickness, t. The calculated stress intensity factor from exact solution formula will be used as a basis from which the stress intensity factor obtained in this study using the boundary element method can be compared with. The Magnification Factor MK, will then be obtained by taking the ratio of the Stress Intensity Factor of a model with welded attachment to a model without welded attachment.